Effect of lysozyme on in vitro emission of CO2 and energy loss of CH4 in bovine - Rodríguez Arenillos, María Gabriela (2022)
The effect of increasing concentrations of Lysozyme chlorhydrate (LC) on in vitro CO2 emission and energy losses associated with enteric methane in fibrous substrate with concentrated feed (Conc.) was evaluated. Three treatments were studied: TC1: lignified guinea grass (Panicum maximun Jacq.), TC2: Concentrated 18 % PC and TC3: 75% grass + 25% concentrated) each at three doses (80,000; 160000 and 320000 IU/kg). Distributed in: T1: Pasture, T1/80: Pasture+LC80000, T1/160: Pasture+CL160000, T1/320: Pasture+CL320000, T2: Conc., T2/80: Conc.+LC80000, T2/160: Conc.+LC160000, T2/320: Conc.+LC320000, T3: Grass+Conc. T3/80: Grass+Conc.+LC80000, T3/160: Grass+Conc.+LC160000, T3/320: Grass+Conc.+LC320000. The incubation times were: 3, 6, 12, 24, 48 and 72 hours. The results indicate that the addition of LC between 80000 and 160000 IU/kg increased (P<0.05) the degradation of grass DM and TC3. The incorporation of 160000 IU/kg in T3/160 reduced CO2 emissions by 72%. The highest CO2 production value (472 ppm) was recorded by T1/160 with 160000 IU/Kg CL. The treatments containing CL (T3/80, T3/160, T3/320) reduced (P<0.05) the production of CO2 (443 ppm) with respect to the control (1710 ppm). Grass with LC at different doses reduced (P<0.05) energy losses associated with methane production by 10.74% (80000 IU/kg) and 14.72% (160000 and 320000 IU/kg). In conclusion, the use of Lysozyme improved the in vitro utilization rate of the diet (75% grass + 25% concentrate) and reduced CO2 emissions and energy losses associated with CH4 emissions.